PROMOTING AND DEVELOPING OF WOMEN ENTREPRENEURSHIP (WITH SPECIAL REFERENCE TO CHENNAI CITY) (CAHIERS MAGELLANES-NS, 2024)
Women run successful enterprises, yet persistent gendered inequalities continue to create major disparities in opportunities to start and grow a business. Women and men entrepreneurs can encounter similar challenges in their economic activities; however, women are faced with an additional set of gender-based barriers that limit their access to resources and opportunities. The purpose of the study promoting and development of women entrepreneurs. The main objectives of the study analyse the various scheme of women entrepreneur’s development and identify the factors influencing to promoting and development women entrepreneurs in Chennai City. The methodology of the study current investigation of study is descriptive method and it draw its conclusion both primary and secondary sources of information. The study is descriptive and analytical. The study both primary and secondary data. This study is carried out with the observation and survey questionnaire methods which are attributes of descriptive research. The data for the study was collected through structured questions. The sample size is 200. A convenience sampling method was used for the study. The data were analysed and SPSS was used to analyse and interpret and required data. The analysis was used for percentage analysis, Ranking method, Chi-square test and Exploratory Factors Analysis. The finding of the study Women Entrepreneurship Development training should be organised to provide opportunities for women to develop their personality. Organise training programmes to develop competencies in production, marketing, leadership, business plan preparation, etc. Encouraging more aspiring women entrepreneurs.